A study on the porter effect of China’s carbon emissions trading policy - Kebei, Shi; Yaxin, Zhang; Tongping, Li (Frontiers in Environmental Science, 2025)
Accomplishing the coordination between economy and environment requires a series of efficient measure so that the Potter effect can be realized. This study, from the perspective of market-government coordination, empirically examines the Porter effect of China’s carbon emissions trading policy using a difference-in-differences approach. The findings reveal that: (1) The carbon emissions trading policy has significantly reduced local carbon emissions by 78.6%, increased regional green total factor productivity by 32.7%, and enhanced scientific and technological innovation by 43.9%, thereby demonstrating a pronounced and strong Porter effect. Robustness checks, including placebo tests and Propensity Score Matching-Difference in Differences estimation, confirmed the validity of these results. (2) Market mechanisms, as measured by carbon prices and market liquidity, only partially facilitate the realization of the Porter effect under the policy. (3) The stronger the administrative intervention by local governments, the more pronounced the policy’s Porter effect. Based on these findings, this study proposes the following policy recommendations: to achieve the dual carbon goals, the government should further expand the carbon emissions trading policy and progressively establish a unified national carbon trading market with cross-sector participation. Additionally, policymakers should address market failures in environmental governance, uphold the synergy between market mechanisms and administrative interventions, thereby fostering a virtuous cycle between environmental protection and economic development.